FROM MILLENNIALS TO 'SILVER ECONOMY': AN ANALYSIS OF TECHNOLOGY READINESS, USER EMANCIPATION, AND AI ADOPTION IN THE SOCIO-ECONOMIC TRANSFORMATION ECOSYSTEM - Asep; Aim Abdulkarim; Meila Yufriana Devi (SOSIOEDUKASI, 2026)
The transition to cybernetic capitalism and the disruption of Artificial Intelligence (AI) have created a reality of "Mixtopia", where utopian efficiency coexists with dystopian threats like data exploitation and the loss of human autonomy. Amid this socioeconomic transformation, it is crucial to understand how different demographic groups, specifically adaptive young entrepreneurs versus the ageing population in the “Silver Economy”, respond to technological disruptions and digital inequalities. This article analyzes cross-generational AI adoption dynamics using the “Technology Readiness and Acceptance Model (TRAM)” and the sociological concept of “Mündigkeit” (emancipation toward autonomy)”. Findings reveal that Millennial and Generation Z entrepreneurs in developing economies share similar pragmatic behaviors; their AI adoption is primarily driven by “perceived usefulness” for business efficiency rather than mere technological novelty. In particular, the Silver Economy is highly vulnerable to digital exclusion. To counter data capitalism and prevent users from becoming passive, "intergenerational learning" is proposed as an essential methodology to foster critical reflection and user emancipation. Ultimately, sustainable economic transformation requires shifting from blind acceptance of technology to critical user adoption.